Plant-Caused Skin Disorders - Janjić, Vaskrsija (Cambridge Scholars Publisher, 2021)
This book covers the basic concepts of phytodermatoses and groups of compounds in plants that have such physiological effects on humans. In order to allow the reader a better understanding of phytodermatoses, skin reactions caused by contact with plants are classified as allergic contact dermatitis, irritant contact dermatitis, contact urticarial, and phytophoto dermatitis. Dermatoses are caused by certain plant constituents that are often classified into groups, such as alkaloids, glycosides, glucosinolates, saponins, phenols, and other compounds. The book also describes 68 plants species tha.